2017
DOI: 10.1002/cjoc.201600748
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Sodium on the Structure‐Performance Relationship of Co/SiO2 for Fischer‐Tropsch Synthesis

Abstract: A series of Co/SiO2 catalysts with different sodium (Na) loadings (0, 0.1, 0.2, 0.5 and 1 wt%) were prepared and evaluated for Fischer‐Tropsch reaction to study the effect of Na on the catalyst structure and catalytic performance. The addition of Na was found to decrease the catalytic activity and hydrocarbon selectivity, but increase CO2 selectivity due to the enhanced WGS activity. The addition of Na also resulted in higher selectivity to oxygenates (alcohols and aldehydes) and O/P ratio as well as the shift… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
20
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 33 publications
3
20
0
Order By: Relevance
“…The chain growth probability is also significantly diminished after the treatments, as shown on Figure 10. These observations are in line with several studies [14,15,[24][25][26] which reported a high productivity in light products and CO 2 on carburized cobalt catalysts, and indicate that their observations were not due to conversion effects. The olefin selectivity decrease is yet contradictory to the conclusions of Zhong et al [69], who obtained high olefin selectivity on Co 2 C nanoprismes.…”
Section: Selectivitysupporting
confidence: 92%
See 2 more Smart Citations
“…The chain growth probability is also significantly diminished after the treatments, as shown on Figure 10. These observations are in line with several studies [14,15,[24][25][26] which reported a high productivity in light products and CO 2 on carburized cobalt catalysts, and indicate that their observations were not due to conversion effects. The olefin selectivity decrease is yet contradictory to the conclusions of Zhong et al [69], who obtained high olefin selectivity on Co 2 C nanoprismes.…”
Section: Selectivitysupporting
confidence: 92%
“…High CH 4 and CO 2 selectivities were also reported by Mohandas et al [24], using a cobalt carbide catalyst under relevant industrial Fischer-Tropsch conditions. A significant CO 2 selectivity was, moreover, observed on Na-promoted Co/SiO 2 catalysts by Dai et al [14], exhibiting a significant Co 2 C content. Additionally, Pei et al [25,26] measured a much higher alcohol selectivity on carburized cobalt catalysts than on a non-carburized catalyst.…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…Furthermore, it has been suggested that the most favorable binding site for Na on metal catalysts is on the step sites, [35] consistent with calculations showing that high index facets of Co, like step sites, have high surface energy [36,37] . We therefore propose that as Na content increases, the fraction of blocked steps sites on the Co metal surface also increases, thus resulting in a greater fraction of Co 2 C formation during reaction, an observation that agrees with other studies of Na effects on Co Fischer‐Tropsch catalysts [38] …”
Section: Resultssupporting
confidence: 90%
“…While E ads [C*] increases, to 713 and 714 kJ mol –1 , respectively, on decoration with PrO 2 , a higher increment, to 714 and 721 kJ mol –1 , was found after deposition of Na 2 O, making the cobalt surface more carbophilic. Reinforcing these computational predictions and in line with previous reports of a facilitated carbide formation upon incorporation of alkali promoters, 77 , 78 XRD analysis of catalysts recovered after the FT tests revealed the development of Co 2 C crystalline domains in 3.0Na-CoRu/AOmM, that is, the catalyst showing the most marked increase in CO 2 selectivity ( Figure S11 ). These results allow thus to surmise that the enhanced carbon affinity and thus a facilitated development of surface carbide species during catalysis underlie the undesired boosting of the WGSR activity observed experimentally for NaO x and other alkali oxides.…”
Section: Resultssupporting
confidence: 89%